Sustainable Management Against Fruit Fly And Borer By Bagging Systems In Mango (Mangifera Indica L.) - Islam, Md Zahurul; Kabir, Md Hafizul; Islam, S M Shahinul (Journal of Bio-Science, 2024)
Mango is the leading seasonal cash crop in Rajshahi, Naogaon and Chapainawabganj and other regions of Bangladesh. But due to fruit fly and borer the important cash crop is prone to attacks of insect pests and diseases its developmental stages. The study has been conducted to find out the effect of pre-harvest fruit bagging against fruit fly and borer on post-harvest quality and shelf life of mango cv. Amrapali. Under this study five different bagging materials were used e.g (i) control (non-bag fruit), (ii) brown paper bag (T1), (iii) white paper bag (T2), (iv) black polythene bag (T3) and (v) white polythene bag (T4). In this case non-bagging fruits were considered as control (T0). The experiment was laid out in randomized complete block design with three replications. Significant variations among the pre-harvest bagging materials in relation to physio-chemical quality attributes and shelf life of mango cv. Amrapali was found. The attributes such as weight, length and breadth of fruit, skin color, moisture content, dry matter content, Vitamin-C, sugar content (reducing, non-reducing and total sugar), total soluble solids content and shelf life were significantly influenced by the bagging materials. All parameters except Vitamin-C of the bagged fruits were higher than that of control fruits. Highly significant difference in respect of shelf life between bagged and non-bagged fruit was observed. The longer shelf life (15.06 days) was observed in brown paper bag whereas the shortest shelf life (7.92 days) was in control fruits. It was observed that all bagging materials were 100% effective against fruit fly and borer attack but all physical and chemical parameters were significantly affected due to apply different bagging materials. Considering all parameters, it was found that brown paper and white paper bagged fruits mangoes appeared to be the best in respect of skin color weight and size of fruit, moisture content, dry matter content, Vitamin-C content, total soluble solids content, and extending shelf life in mango cv. Amrapali. J. Bio-Sci. 32(1): 41-55, 2024